Impact of invasive ventilation on survival when non-invasive ventilation is ineffective in patients with Duchenne muscular dystrophy: A prospective cohort. (June 2016) - Boussaïd, Ghilas; Lofaso, Frédéric; Santos, Dante Brasil; Vaugier, Isabelle; Pottier, Sandra; Prigent, Hélène; Bahrami, Stéphane; Orlikowski, David
Abstract: Background: Many patients with DMD undergo tracheostomy. Tracheostomy is associated with certain complications, however its effect on prognosis is not known. Methods: The relationship between type of mechanical ventilation and survival at 12 years was evaluated in a prospective cohort of patients with Duchenne muscular dystrophy followed in a French reference center for Neuromuscular Diseases. Cox proportional-hazards regressions were used to estimate the hazard ratios associated with risk of switching from non-invasive to invasive ventilation, and with risk of death. Results: One hundred and fifty patients were included. Initial use of invasive ventilation was associated with an episode of acute respiratory failure (p < 0.0001) and with a severe clinical status (p < 0.05). Risk of death was associated with swallowing disorders (2.51, IC [1.12–5.66], p < 0.03) and cardiac failure (p < 0.05) but not with type of mechanical ventilation. Conclusion: Switching to invasive ventilation is appropriate when non-invasive ventilation is ineffective. Highlights: NIV failure was associated with a severe clinical and respiratory state. Transition to VI is crucial, when NIV becomes inefficient. Swallowing and cardiac disorders improve the risk of death in patients with DMD.